Immune signature of Chlamydia vaccine CTH522/CAF®01 translates from mouse-to-human and induces durable protection in mice - Anja Weinreich Olsen; Ida Rosenkrands; Christina S. Jacobsen; Hannah M. Cheeseman; Max P Kristiansen; Jes Dietrich; Robin J. Shattock; Frank Follmann (2024)
Abstract The clinical development of an effective Chlamydia vaccine requires in-depth understanding of how well protective pre-clinical immune signatures translate to humans. Here, we report a comparative immunological characterization of CTH522/CAF®01 in female mice and humans. We find a range of immune signatures that translate from mouse to human, including a Th1/Th17 cytokine profile and antibody functionality. We identify vaccine-induced T cell epitopes, conserved among Chlamydia serovars, and previously found in infected individuals. Using the mouse model, we show that the common immune signature protected against ascending infection in mice, and vaccine induced antibodies could delay bacterial ascension to the oviduct, as well as development of pathology, in a T cell depleted mouse model. Finally, we demonstrate long-lasting immunity and protection of mice one year after vaccination. Based on the results obtained in the present study, we propose to further investigate CTH522/CAF®01 in a phase IIb study.